1996
DOI: 10.1063/1.471475
|View full text |Cite
|
Sign up to set email alerts
|

Growth and collapse of structural patterns in the hydrogen bond network in liquid water

Abstract: Articles you may be interested inApplication of the reference interaction site model theory to analysis on surfaceinduced structure of water A dynamic effect of structural water: Anomalous melting and premelting transition in AT DNA AIP Conf. Proc. 342, 209 (1995); 10.1063/1.48828 ''Ab initio'' liquid water and the conductive state of the excess electron AIP Conf.Intermittent and chaotic motions of the hydrogen bond network are studied with the molecular dynamics ͑MD͒ simulation. By analyzing the fluctuation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
152
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(169 citation statements)
references
References 30 publications
1
152
0
Order By: Relevance
“…Using the local structure index (LSI) (7,51) to identify high (I > 0.03) and low (I < 0.03) structured local coordinations results in an amount of high-LSI molecules of ∼50% at ambient conditions and a rapid decrease of this number with increasing p, T. However, a spatial statistical analysis of these subpopulations also shows no spatial correlations beyond r ) 5 Å even for the high-LSI molecules (SI Text), which indicates that molecules with different local environments are present at all simulated temperatures and pressures but are not spatially correlated beyond their characteristic distances (i.e., the second coordination shell). This is in line with the findings of English et al (4).…”
Section: Resultsmentioning
confidence: 99%
“…Using the local structure index (LSI) (7,51) to identify high (I > 0.03) and low (I < 0.03) structured local coordinations results in an amount of high-LSI molecules of ∼50% at ambient conditions and a rapid decrease of this number with increasing p, T. However, a spatial statistical analysis of these subpopulations also shows no spatial correlations beyond r ) 5 Å even for the high-LSI molecules (SI Text), which indicates that molecules with different local environments are present at all simulated temperatures and pressures but are not spatially correlated beyond their characteristic distances (i.e., the second coordination shell). This is in line with the findings of English et al (4).…”
Section: Resultsmentioning
confidence: 99%
“…To quantify the degree of inhomogeneity in the local molecular environments of liquid water, we have utilized an order parameter introduced by Shiratani and Sasai 31,32 , which associates a local structure index (LSI) to the individual water molecules comprising the liquid. In essence, the LSI order parameter is the mean-squareddeviation among the radial distances corresponding to the set of molecules that surround a given water molecule.…”
Section: B Local Structure Index (Lsi)mentioning
confidence: 99%
“…In this regard, recent studies have shown that the local structure index (LSI) 31,32 is a very insightful order parameter that can be employed to characterize the LDL and HDL molecular environments 23 . For instance, the distribution of the LSI order parameter was found to be bimodal in the corresponding inherent potential energy surface (IPES) of both supercooled and ambient liquid water [33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
“…Several schemes to determine whether an H-bond is present or not have been suggested, but the purely geometrical definitions have thus far proven to be insufficiently sensitive. 7 A scheme that provides a bimodal distribution of LDL/HDL local structures, 51,52 when considering the inherent structure 53 of simulated water, is the local structure index 54 (LSI). This order parameter accounts for the structure and coordination of the first and second solvation shells.…”
mentioning
confidence: 99%